Do foreign exchange administration rules strengthen the currency value? Policy lessons from an emerging market - Lau, Wee-Yeap; Yip, Tien-Ming (The Economics and Finance Letters, 2023)
After the announcement of the US presidential election result on 8 November 2016, many ASEAN currencies became volatile relative to the US Dollar (USD). Despite being an emerging market, Malaysia took an unprecedented step. It implemented new rules in December 2016 to halt the decline of the Malaysian Ringgit (MYR). Under the new rules, exporters must convert 75 per cent of export proceeds from foreign currency to local currency with a licensed financial institution. Using the sample period from September 2015 to July 2018, this study examined the impact of the Supplementary Notice on Foreign Exchange Administration (FEA) rules on MYR. Our study revealed, first, that despite the initial uneasiness of Multinational Companies (MNCs), the FEA rules effectively strengthened the MYR against the USD and other major currencies; second, the rule mitigated the depreciation of FDI and crude oil price on MYR; third, the results were robust in terms of model specification and estimation. The policy suggestion is made that the export conversion rule should be applied to foreign firms in Malaysia and domestic oil exporters, as it would mitigate the depreciation impact of the increase in FDI and crude oil price. Malaysia’s experience provides policy lessons for emerging economies to emulate when facing unexpected exchange rate volatility.